Adsorption of As(OH)3 on the (001) Surface of FeS2 Pyrite: A Quantum-mechanical DFT Study - Blanchard, M.; Wright, Kate; Gale, Julian; Catlow, R. (American Chemical Society, 2007)
We have performed first-principles calculations based on density functional theory (DFT), to model interactions of arsenic with FeS2 pyrite. An understanding of pyrite reactivity on the atomic scale is needed to predict the availability and mobility of arsenic in reducing conditions. Modeling of surface processes, however, requires large systems involving a vacuum part under periodic conditions, which makes plane-wave DFT methods very expensive computationally. We take advantage here of the use of localized pseudo-atomic orbitals as implemented in the DFT code SIESTA to model bulk surface reactions of pyrite with arsenic. The latter method shows good agreement with the available data (theoretical and experimental) for the structure of FeS2 pyrite, the arsenic substitution in the bulk pyrite, as well as the energetics and relaxation of the (001) pyrite surface. This method has been employed to investigate the adsorption of As(OH)3 on the (001) surface and the potential arsenic segregation with respect to the same surface. Our calculations suggest that the best adsorption configuration is a bidentate complex with two Fe-O bonds, which is similar to the first surfacecomplexes observed in arsenite adsorption experiments. Once the arsenic atom is incorporated at the surface by substitution with a sulfur atom, it will readily incorporate into the bulk during pyrite growth; no segregation of arsenic with respect to the (001) pyrite surface is expected.